Learning Perl on Win32 systems - Schwartz, Randal L. (O'Reilly, 1997)
In this smooth, carefully paced course, leading Perl trainers and a Windows NT practitioner teach you to program in the language that promises to emerge as the scripting language of choice on NT. With a foreword by Larry Wall, the creator of Perl, this book is the "official" guide for both formal (classroom) and informal learning. Based on the "llama book," Learning Perl on Win32 Systems features tips for PC users and new, NT-specific examples.
"Windows NT"--Cover. - Includes bibliographical references and index. - Print version record
Keywords: Microsoft Win32; Perl (Computer program language); Perl (Langage de programmation); COMPUTERS; Programming Languages; Perl; PERL; Engineering & Applied Sciences; Computer Science; Perl (langage de programmation)